Teori Kelangkaan Ibnu Khaldun dan Relefansinya dengan Ekonomi Indonesia - Suyadi, Suyadi; Wahyudi, Amin (Fakultas Syariah INSURI Ponorogo, 2022)
The purpose of this study is to describe the extravagant behavior studied from Ibn Khaldun's theory. We find a lot of extravagant behavior in Indonesia, where the majority of the population is Muslim. Wasteful behavior actually does not only occur in Indonesia but also occurs in developed countries. If this wasteful behavior is continuously carried out by the community, what happens can result in poverty. Meanwhile, Ibn Khaldun often criticized the extravagant behavior of advanced societies, both explicitly and implicitly. The method of writing this article is a literature study, namely looking for sources through the Library. As a tipping point where the economic life of society and civilization declines.